Menduga Bobot Badan Sapi Bali Jantan Berberat di Atas 500 Kilogram (THE ESTIMATION OF LIVE WEIGHT OF BALI BULLS ABOVE 500 KILOGRAMS) - Sampurna, I Putu; Batan, I Wayan (Jurnal Veteriner; Vol 1 No 1 (2000), 2016)
Menduga Bobot Badan Sapi Bali Jantan Berberat di Atas 500 Kilogram   (THE ESTIMATION OF LIVE WEIGHT OF BALI BULLS ABOVE 500 KILOGRAMS)
Keywords: Bali bulls, live weight, regession, estimation